STRATEGI KOMUNIKASI MELIBATKAN MASYARAKAT DALAM PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BINJAI - sihombing, Dermawaty (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas HKBP Nommensen, 2025)
This study aims to analyze the communication strategy for involving the public in public services at the Population and Civil Registration Office of Binjai City to improve public services. The method used in this study is a descriptive qualitative approach. Researchers conducted observations, direct interviews with the community, discussion forums with community organizations, service users, the Education Office, academics, and the mass media. Data analysis techniques were also conducted through documentation studies. After obtaining the results, researchers analyzed the data using strategic theory, Harold Laswell's communication theory, and communication psychology. The results indicate that the Population and Civil Registration Office of Binjai City has implemented a public communication strategy, focusing on planning, implementation, and evaluation, presented in an engaging manner through communication media.